Lenalidomide and dexamethasone in treatment of patients with relapsed and refractory multiple myeloma - analysis of data from the Czech Myeloma Group Registry of Monoclonal Gammopathies - Maisnar, V; Stefanikova, Z; Spicka, I; Pour, L; Minarik, J; Flochova, E; Radocha, J; Gregora, E; Stecova, N; Jelinek, T; Jungova, A; Kralikova, E; et al. (Neoplasma, 2019)
Lenalidomide (LEN) is an immunomodulator with clinical activity against myeloma cells. Based on the pivotal phase 3 trials MM-009 and MM010, the combination of lenalidomide and dexamethasone(DEX) was approved for patients with multiple myeloma who received at least one prior therapy. Here, we evaluated LEN/DEX therapy in unselected population and subsequently in selected sub-groups of patients with relapsed/refractory multiple myeloma followed in the Registry of Monoclonal Gammopathies of the Czech Myeloma Group. Altogether 858 patients were treated with LEN/DEX in the Czech Republic and Slovakia until end of 2017. The analyzed sub-groups were defined as patients with high risk cytogenetic aberrations and patients with relapsed and refractory MM. The overall response rate (ORR; partial remission or better response, PR) in the whole group of patients was 46.3% for all lines of therapy, 26.4% for high-risk group and 32.1% for relapsed and refractory group. Medians of overall survival (OS) in the same cohorts were as follows: 25.6, 15.7 and 18.5 months, progression free survival (PFS) was: 11.2, 6.4 and 9.0 months respectively. The most common adverse events were hematologic and infectious. In conclusion we found that our results correlated with those found in other studies in terms of response rates, survival measures, and also of treatment toxicity.
Keywords: Registries; Dexamethasone; lidé; Treatment Outcome; Slovenská republika; Humans; Antineoplastic Combined Chemotherapy Protocols; Multiple Myeloma; Lenalidomide; Czech Republic; protinádorové látky; Antineoplastic Agents; protokoly protinádorové kombinované chemoterapie; dexamethason; registrace; lenalidomid; mnohočetný myelom; výsledek terapie; analýza přežití; Česká republika; Survival Analysis; Slovakia